Characterization of 1,8-diazabicyclo(5.4.0)undec-7-ene-hydroxyl-based ionic liquid for CO2 capture - Syarafana O. Amat; Normawati M. Yunus; Cecilia D. Wilfred (Royal Society Open Science)
Six 1,8-diazabicyclo(5.4.0)undec-7-ene-based ionic liquids (ILs) linked with ethyl or propyl hydroxyl cations, coupled with thiocyanate, dicyanamide and bistriflimide anions, were synthesized through a two-step reaction: quaternization and ion exchange. The characterization of the ILs was carried out using 1H and 13C nuclear magnetic resonance spectroscopy (NMR) and Fourier-transform infrared spectroscopy (FTIR). The NMR results confirmed the structures of all the ILs, and these were supported by the FTIR results. In addition, the physicochemical properties, namely thermal stability, density and refractive index, were determined. The effects of the chain length in the cation and the identity of the anion on CO2 absorption were studied in a pressure drop equipment at different pressures. It was found that CO2 sorption increased with increasing pressure and the number of nitrile groups present. The highest CO2 sorption is reported to be 0.96 mol CO2 mol−1 IL at 20 bar.